Pancreatic Desmoplastic Small Round Cell Tumour. A Rare Presentation of Painful Obstructive Jaundice - Subasinghe, Duminda; Keppetiyagama, Chathuranga Tisara; Sudasinghe, Hemantha; Perera, Niranthi; Skandarajah, Thurairajah; Sivaganesh, Sivasuriya (JOP. Journal of the Pancreas, 2014)
Context Pancreatic desmoplastic small round cell tumour (DSRCT) is an extremely rare malignancy of which very few reports exist. It follows an aggressive course and has a dismal prognosis. Case report A twenty-four-year-old male presented with a one-month history of rapidly progressive obstructive jaundice associated with abdominal pain suggestive of a biliary colic. Contrast-enhanced CT (CECT) of the abdomen revealed a pancreatic head mass. He underwent a pancreaticoduodenectomy and adjuvant chemotherapy and is disease free one year after surgery. Conclusion This is the first reported case of a pancreatic head DSRCT, discovered in a young male investigated for a short history of painful obstructive jaundice. Image: Tumor cells showing cytokeratin and neurone specific enolase positivity.